PRICE CASH FLOW RATIO, NET GEARING RATIO, CURRENT RATIO, DAN RETURN SAHAM PERUSAHAAN SUB SEKTOR KONSTRUKSI - Aldina Murti; Dhistianti Mei Rahmawantari; Rachmaniar Myrianda Dwiputri (Jurnal Ekonomi dan Industri, 2025)
This research aims to determine the effect price cash flow ratio, net gearing ratio, and current ratio to return shares in construction sub-sector companies listed on the Indonesia Stock Exchange for the period 2018 - 2023. This research was conducted by collecting data from the Indonesia Stock Exchange (BEI). The data analysis technique in this research uses quantitative and descriptive research methods. The sampling method used in this research is purposive sampling, by taking data from financial reports and annual share price indexes of construction sub-sector companies from 2018 to 2023. The total sample used was 54 data which was then processed by researchers using panel data regression analysis. This research found that price cash flow ratio, net gearing ratio, and current ratio simultaneously influence return shares. Price cash flow ratio partially has no effect on return shares. Net gearing ratio partially influences return shares. Current ratio partially influences return shares.